Trends of Rainfall Pattern in the Island Province of Catanduanes, Philippines - Engr. Dexter M. Toyado, MM (International Journal of Engineering and Management Research, 2022)
The Island of Catanduanes is located in the eastern most fringe of Luzon considered to be the doorstep of typhoon path. The rainfall in the province is important in producing agricultural food to make life in the province sustainable. Hence, it is necessary to establish how the effect of climate change variable on the availability of water in the island, so that impending extreme drought or flooding will be mitigated. In addition to that, Climate change in the island has an impact on human activity, and a treat from flooding of variable weather pattern like seasonal monsoon rain and inter tropical convergence zone develop near the island. Using the data from the PAGASA-DOST, Climatology and Agro meteorology Division (CAD) of April 2020, from the Virac Doppler and Radar Weather in Catanduanes. Synoptic data were used to evaluate the rainfall for the last 30 years. The rainfall pattern caused by the southwest monsoon (Habagat) most from June to September gives an average of 73.08mm for 3 decades. Northeast monsoon (Amihan) usually arrives on November and ends on March having an average rainfall of 103.78mm for 3 decades. It has been shown that the rainfall is increasing every year, the annual rainfall trends will increase of up to 10.76mm in the next 10 years. Studying the rainfall pattern and temperature will give us more precise assessment of the climatic condition in the island and give the community and the government the proper information for mitigating and planning on how we can handle climate change.